2016
DOI: 10.1093/aob/mcw215
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenesis and functions of saxophone stem inAcrocomia aculeata(Arecaceae)

Abstract: The saxophone stem represents an important adaptation of A. aculeata to anthropogenically impacted and/or dry environments by promoting the burial of both the shoot meristem and storage reserves, which allows the continuous growth of aerial organs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
2
3
0
1
Order By: Relevance
“…The embryonic axis of oblique position is in the proximal region, composed by two meristematic regions, the shoot meristem (plumule) and the root meristem. In the region of the root meristem, cells of smaller diameter, intensely ruddy, and in the shape of a shell are observed, the radicle; in the shoot meristem, which corresponds to the plumule, there are three leaf primordia that will form the first and second cataphyll and the eophyll, sequentially (Figures 3B-D and 4A), lined by a protoderm, as also observed in Acrocomia aculeata, Euterpe precatoria, and Syagrus inajai (Souza et al, 2017;Aguiar and Mendonça, 2003;Genovese-Marcomini et al, 2013). The distal region, which corresponds to the cotyledon blade, has a haustorial function, with an irregular surface and provascular bundles (Figures 3E and 4C-D).…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…The embryonic axis of oblique position is in the proximal region, composed by two meristematic regions, the shoot meristem (plumule) and the root meristem. In the region of the root meristem, cells of smaller diameter, intensely ruddy, and in the shape of a shell are observed, the radicle; in the shoot meristem, which corresponds to the plumule, there are three leaf primordia that will form the first and second cataphyll and the eophyll, sequentially (Figures 3B-D and 4A), lined by a protoderm, as also observed in Acrocomia aculeata, Euterpe precatoria, and Syagrus inajai (Souza et al, 2017;Aguiar and Mendonça, 2003;Genovese-Marcomini et al, 2013). The distal region, which corresponds to the cotyledon blade, has a haustorial function, with an irregular surface and provascular bundles (Figures 3E and 4C-D).…”
Section: Resultssupporting
confidence: 57%
“…The endosperm is white, with an oily, solid, and abundant appearance and is in direct contact with the seed coat (Figure 1B), a characteristic also observed in Butia capitata (Oliveira et al, 2013) and in Acrocomia aculeata (Souza et al, 2017).…”
Section: Resultsmentioning
confidence: 64%
“…The last phases exhibit an increase in growth of the shoot, taproot, and haustorium, as well as a reduction in water content (Mazzottinidos-Santos et al 2017). Acrocomia seedlings develop a tuberous underground system (i.e., saxophone stem structure) that stores reserves and results from the growth, curvature, and expansion of the embryo (Souza et al 2017b). This structure influences the distribution of the root system (Moreira et al 2019).…”
Section: Seedling Developmentmentioning
confidence: 99%
“…The positive geotropic growth of the cotyledonary petiole that promotes the burial of the vegetative axis is considered an important strategy for protection against desiccation, fire, herbivory, and anthropic impacts, and shows great adaptive value in dry environments (Souza et al, 2017;Xiao et al, 2019). We observed that the vegetative axis of A. vitrivir becomes buried several centimeters below the soil surface after germination, where it remains protected, with the emission of the first eophyll occurring only approximately 60 days later.…”
Section: Structural and Ecophysiological Aspects Of Shading Responsesmentioning
confidence: 78%